Democracy and Political Parties In Brazil: Where the Women? - Santos, Jahyra Helena Pequeno dos (2016)
This article proposes to verify the absence of women inthe Brazilian political sphere, spedifically in political parties. The hypothesis is that the parties are women inthe envarionment? It is noticed that contemporary democracy applies to a different society. The parties, as a means of access to political offices were, and often still are, seen as one belonging to men vacancy opportunity, thus consolidating the idea that women should occupy the the private sphere.